If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 = 1 + 2b Solving 9 = 1 + 2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2b' to each side of the equation. 9 + -2b = 1 + 2b + -2b Combine like terms: 2b + -2b = 0 9 + -2b = 1 + 0 9 + -2b = 1 Add '-9' to each side of the equation. 9 + -9 + -2b = 1 + -9 Combine like terms: 9 + -9 = 0 0 + -2b = 1 + -9 -2b = 1 + -9 Combine like terms: 1 + -9 = -8 -2b = -8 Divide each side by '-2'. b = 4 Simplifying b = 4
| 3x+2(x+2)=5x+4 | | -2.5s=25 | | 2x+2+7x=-6x-2x | | .4x-8+.5x=19 | | 2(x+1)=3(x+4) | | 4+2i=4 | | 12y=1x+b | | -8g=.48 | | 0.6r=.0005 | | -7y=-6.3 | | 2(x+1)=3(x+4)+10 | | 0.6=r+.0005 | | (3x^2-2x^2+2x-5)*x+1= | | x+(-28)=53 | | .3k=-12 | | 14=6-4y | | 3(10x+4)=8(3x+6) | | z^2=z-12 | | 5r=-.15 | | 3x+2(x+2)=5-4x+2 | | (2x-5)/6-(3x-2)/3=(2x-5)/2 | | .0005=0.6r | | 3x+14=7x+2 | | -6x+5=77+2x | | 20y+3=7 | | 5x-7=-7x+29 | | .0005=0.6 | | -2x-10=-7-5x | | 0.75+2(x-0.5)=2p | | 7(5t-1)-18t=12t-(3-t) | | x^2+4x=22 | | -2-2x=3x+3 |